Academic Achievement and the Implications for Prison Program Effectiveness and Reentry - Silver, Ian A. (Criminal justice and behavior, 2020)
The current study examines how academic achievement—measured as verbal and math performance—is associated with prison programming and reentry. We assess how academic achievement might be directly associated with recidivism and whether this occurs indirectly by moderating the effectiveness of in-prison programs. Using a statewide subsample of incarcerated individuals (N = 13,536), the results illustrated that academic achievement directly and indirectly affected the likelihood of recidivism. Lower academic achievement was associated with a higher likelihood of recidivism immediately upon reentry, but was also linked to greater effectiveness of prison programs aimed at reducing recidivism. The reduction in the likelihood of reincarceration associated with program participation was greater for individuals with lower academic achievement compared with those with higher academic achievement. The results underscore how individual differences can lead to heterogeneous outcomes and emphasize the need to target those individuals most likely to struggle with the practical barriers of reentry.